TRANSNATIONAL LAW AND THE IBT COURSE - Purba, A. Zen Umar (UI Scholars Hub, 2015)
Today business transactions transcending national borders need a new concept, namely transnational business transactions. It deals not only with private, but also with public issues; This in line with the birth of transantional law, as firstly expressed by Judge Jessup Philip in 1956. This article aims to discuss the importance of including the international bussiness transactions (“IBT”) course in Indonesia’s legal education. It concludes that transnational law, as reflected by IBT is nowadays an important basis to give understanding to the students on how law makes guidance and fence for commercial transactions across the border.